A descriptive analysis of anglicism used in Ecuadorian magazines - Rocha Suárez, Rafael Edmundo (2012)
The subject of this research is “A descriptive analysis of anglicisms in ecuadorian magazines”, and it was carried out in Guayaquil, through the comprehensive reading of magazines whose topics attract much attention and ensure a high number of readers of most ages and any social stratum. Thus, the types of magazine selected as a sample for this study were: cultural, scholarly and general interest. To conduct this research, two magazines of each type were selected, and reading techniques as scanning and skimming were used. The first step was to identify the words considered anglicisms. The second step was to find out how the anglicism works within the sentence, that is, its function and meaning in the read context. After reading the material chosen for this research, an analysis of the linguistic phenomenon of anglicisms was made. In many cases, are necessary when the equivalent in Spanish Language does not exist, especially in technological, medical or scientific fields. Unfortunately, the use of anglicisms has dramatically increased in the past few years. The use of foreign terms should be just a temporary solution to the lack of an equivalent in Spanish. “La Real Academia de la Lengua Española” should analyze the situation, and issue the necessary adaptations to these terms, using the same media in which we get the anglicisms, with the aim of maintaining the purity of language and identify it with our idiosyncrasy.